Challenges Facing Kenyan Accountants in Implementing Digital Accounting Platforms and Strategies for Overcoming Them - Catherine Mosiara Kenyatta; Rizky Parlika (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Indubitably, digital accounting platforms have proven to be a key element in financial management, especially in the contemporary era. They not only promise but guarantee improved accuracy, analytical depth, and reduced delays. In Kenya, the popularity of cloud-based accounting, AI-powered analytics, and enterprise-resource modules is quickly growing, although adoption still remains uneven across organization sizes, regions, and sectors. This journal’s primary objective was to explore the numerous challenges Kenyan accountants encounter when implementing digital accounting platforms and the strategies they utilize to address and overcome these challenges. Regarding methodology, the paper reviews the existing body of literature, including expert reviews, policy documents, and professional reports, to evaluate six critical barriers: infrastructural limitations, change resistance, financial constraints, human capital shortages, ambiguities in ethical and regulatory areas and the challenges that impact technical integration. It also includes a discussion of the most practical plans of action that practitioners in the field of accounting can employ to adapt to the current and ever-evolving landscape. This thorough analysis concludes that the sustainable digitalization of the accounting sector in Kenya highly depends on a concerted effort from educational institutions, industry stakeholders, government agencies, and professional bodies. It provides pragmatic recommendations for policymakers and provides suggestions for areas of further research, with a deep emphasis on phased implementation, capacity building, across-the-board empirical research, boosted investment in critical and resilient infrastructure, and functional governance frameworks.